Patient-Physician Discussions of Colorectal Cancer Screening: Delivery of the 5 ‘As’ in Practice - Lafata, Jennifer Elston (Am J Prev Med, 2006)
BACKGROUND: The US Preventive Services Task Force advocates for shared decision-making and 5As framework (assess, advise, agree, assist and arrange) for preventive health recommendations. PURPOSE: To describe patient-physician colorectal cancer (CRC) screening discussions, evaluate concordance with 5As framework, and test whether discussion content varies by patient adherence to prior recommendation. METHODS: Direct observation of periodic health examinations in 2007-2009 among primary care patients aged 50-80 due for CRC screening. Qualitative content analyses used to code office visit audio-recordings for occurrence of 5As and other discussion content. RESULTS: 97% of visits contained CRC screening discussion; 31% of these contained evidence of patient non-adherence to prior physician recommendation for CRC screening. While 59% of visits provided some assistance (i.e., help scheduling a colonoscopy or delivery of stool cards), the first three steps of 5As (assess, advise, and agree) were rarely comprehensively provided (1-21%). Only 3% included the recommended last step, arrange follow up. Patients non-adherent to a prior recommendation were significantly (P<0.05) less likely to have the reason(s) for screening discussed (37% vs, 65%) or be told endoscopy clinic would call to schedule colonoscopy (19% vs. 27%), and significantly more likely to have fecal occult blood testing (FOBT) (34% vs. 25%) or FOBT and colonoscopy recommended (24% vs. 14%) and a screening plan negotiated (21% vs. 14%). CONCLUSIONS: Most patients due for CRC screening discuss screening with their physician, but with limited application of 5As approach. Opportunities to improve CRC screening decision-making are great, particularly among those non-adherent with prior recommendations.